Analysis of Public Figure Dwi Handa's Online Identity: Analisis Identitas Online Tokoh Publik Dwi Handa - Agustina, Novita Dwi; Sabella, Alief Syahda (Universitas Muhammadiyah Sidoarjo, 2025)
Dwi Handayani has successfully created a strong and likable online persona. Through good relationships with her audience and a consistent content approach, she has effectively managed contextual breakdowns in her digital presence. This analysis examines how Dwi Handayani has built and maintained her online identity, managed interactions with diverse audiences, and navigated the challenges related to online reputation and privacy concerns. The findings suggest that while Handayani has established a robust online presence, there are significant areas where further strategic measures are required to protect her privacy and reputation. Highlights: Consistent Branding & Engagement – Dwi Handayani maintains a strong online persona through consistent content and active audience interaction. Context Management – She effectively navigates diverse audience expectations, minimizing misunderstandings in her digital presence. Privacy & Reputation Risks – Despite her success, further strategies are needed to enhance privacy protection and safeguard her online reputation. Keywords: Dwi Handayani, Online Persona, Social Media, Community Management, Privacy, Reputation